2020
DOI: 10.1097/ta.0000000000002846
|View full text |Cite
|
Sign up to set email alerts
|

Prehospital end-tidal carbon dioxide predicts massive transfusion and death following trauma

Abstract: BACKGROUND The lack of an accurate marker of prehospital hemorrhagic shock limits our ability to triage patients to the correct level of care, delays treatment in the emergency department, and inhibits our ability to perform prehospital interventional research in trauma. End-tidal carbon dioxide (ETCO2) is the measurement of alveolar carbon dioxide concentration at end expiration and is measured noninvasively in the ventilator circuit for intubated patients in continuous manner. Several hospital-ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
19
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 21 publications
0
19
0
1
Order By: Relevance
“…In addition, two other recent studies demonstrated that prehospital ETCO 2 was predictive of the need for blood transfusion in trauma patients. 9,11 These prior works were limited by relatively small numbers and were performed at single institutions. Our study confirms similar results but has the advantage of significantly larger numbers and a diverse 2.9 ± 1.9 2.9 ± 1.9 3.5 ± 1.9 Min-max 0.0-9.0 0.0-9.0 0.0-6.0 Median (IQR group of trauma centers contributing data leading to increased generalizability.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, two other recent studies demonstrated that prehospital ETCO 2 was predictive of the need for blood transfusion in trauma patients. 9,11 These prior works were limited by relatively small numbers and were performed at single institutions. Our study confirms similar results but has the advantage of significantly larger numbers and a diverse 2.9 ± 1.9 2.9 ± 1.9 3.5 ± 1.9 Min-max 0.0-9.0 0.0-9.0 0.0-6.0 Median (IQR group of trauma centers contributing data leading to increased generalizability.…”
Section: Discussionmentioning
confidence: 99%
“…[5][6][7][8] However, studies of ETCO 2 in the prehospital setting have been limited to small single center series. [9][10][11] Consequently, we conducted a multicenter study with the hypothesis that prehospital ETCO 2 values will be predictive of mortality and need for massive transfusion (MT) following injury in intubated patients.…”
mentioning
confidence: 99%
“…It is measured noninvasively either in the ventilator circuit of intubated patients or with specialized nasal cannulas in nonintubated patients. End-tidal carbon dioxide is widely available across emergency medical services agencies and holds promise as prehospital levels have been shown to correlate with mortality and the need for massive transfusion or early death (Campion et al, 2020).…”
Section: End-tidal Carbon Dioxidementioning
confidence: 99%
“…Nevertheless, low ETCO 2 in trauma is unlikely to be the direct cause of mortality, rather it reflects more severe hemorrhagic shock and inadequate cardiac output to transfer CO 2 from the blood to alveoli, despite systemically elevated PaCO 2 . 12 It is therefore possible that some of the association between low ETCO 2 and 90-day mortality could be related to a higher burden of hemorrhage (and inaccurate estimations of blood loss) in the low ETCO 2 group, rather than being causally connected.…”
mentioning
confidence: 99%
“…Néanmoins, un ETCO 2 bas en cas de traumatisme est peu probablement la cause directe de la mortalité; il est plutôt le reflet d'un choc hémorragique plus sévère et d'un débit cardiaque insuffisant pour transférer le CO 2 du sang aux alvéoles, en dépit d'une PaCO 2 systémique élevée. 12 Il est donc possible qu'une part de l'association entre l'ETCO 2 bas et la mortalité à 90 jours soit liée aux conséquences de l'hémorragie (et à une estimation incorrecte de la perte sanguine) dans le groupe ETCO 2 bas, plutôt qu'à un lien causal.…”
unclassified